To solve this system of equations, we can subtract the second equation from the first equation to eliminate y:
6x - 3y = -6
9x - 3y = -18
(6x - 3y) - (9x - 3y) = -6 - (-18)
6x - 3y - 9x + 3y = -6 + 18
-3x = 12
x = -4
Now that we have found the value of x, we can substitute it back into one of the original equations to solve for y. Let's use the first equation:
6(-4) - 3y = -6
-24 - 3y = -6
-3y = -6 + 24
-3y = 18
y = -6
Therefore, the solution to the system of equations is x = -4 and y = -6.
solve they system equation
6x-3y=-6
9x-3y=-18
1 answer